Struktur Vegetasi dan Nilai Ekonomi Hutan Mangrove Teluk Youtefa, Kota Jayapura, Papua - Nurtanti HAndono; Rosye H.R. Tanjung; Lisye I. Zebua (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
Increasing population may result in excessive changes of land use and natural resource utilization. Local communities of mangrove forest areas have been dependent heavily on forest conditions to survive. Conversion of forest to development requirements is apparently to affect the structure and income of local communities who live traditionally in the region. The purpose of the study is to understand the structure of mangrove forest vegetation and changes of people's income depending their live on mangrove forests in the Bay of Youtefa, Jayapura. Sampling method was purposive sampling of respondents and mangrove vegetation analysis was conducted using line transect method. The plot size were 10 x 10 m2; 5 x 5 m2; and 2 x 2 m2 used for viewing the ecological importance valua index (IVI) of tree, stake and seedling. The results showed that there were 10 known species of mangrove dominated by Rhizophora apiculata, R. mucronata and R. stylosa respectively. R. mucronata dominated the area and has the highest importance value index (IVI) level. Development structure including means of transportation (flying bridge) have a major impact on the local community Increasing economic losses. There is a decrease of direct income of communities as much as 2.05 billion per year (from 5.65 billion to 3.61 billion per year).Key words: mangrove ecosystem, vegetation structure, economic value, Jayapura.